2022
DOI: 10.22159/ijcpr.2022v14i1.44110
|View full text |Cite
|
Sign up to set email alerts
|

Formulation Optimization, Characterization and in Vitro Anti-Cancer Activity of Curcumin Loaded Nanostructured Lipid Carriers

Abstract: Objective: The present study was aimed at preparing stable lyophilized curcumin loaded nanostructured lipid carriers (NLCs). The optimized lyophilized curcumin loaded NLCs were characterized and evaluated for various quality control parameters. Methods: The optimized curcumin loaded NLCs were prepared by modified hot emulsification using precirol ATO 5 (PRE), capmul MCM C8 EP (CAP) as solid and liquid lipids, respectively. The combination of tween 80 (T80) and solutol HS 15 (SHS) were used as an emulsifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In contrast the second method, the drugs are conjugate to the LPHNP system with the help of hydrolyzable linker and this drug-conjugate linker gets hydrolyzed upon reaching the cancer cell resulting in the drug are released separately. According to Sengupta et al, the LPHNPs for multi-drug delivery containing an antiangiogenesis and another chemotherapeutic drug, resulting one inhibit the growth of tumor cells by cutting the blood supply to the cell and another kill the existing tumor cell 48 .…”
Section: Combinational Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast the second method, the drugs are conjugate to the LPHNP system with the help of hydrolyzable linker and this drug-conjugate linker gets hydrolyzed upon reaching the cancer cell resulting in the drug are released separately. According to Sengupta et al, the LPHNPs for multi-drug delivery containing an antiangiogenesis and another chemotherapeutic drug, resulting one inhibit the growth of tumor cells by cutting the blood supply to the cell and another kill the existing tumor cell 48 .…”
Section: Combinational Drug Deliverymentioning
confidence: 99%
“…Ex. The delivery of Small interfering Ribonucleic acid to the cancer cells that initiate the RNA interference pathway to block the protein expression into the tumor initiation and progression 48 . The formulation method for developing a Small interfering Ribonucleic acid delivery system is some as a Deoxyribonucleic acid (DNA) delivery system (Polyplexes and Lipoplexes) 42 but Deoxyribonucleic acid (DNA) delivery has some limitations like poor stability during oral or systemic administration thus to overcome this problem develop a new system called Small interfering Ribonucleic acid (SiRNA) development.…”
Section: Si-rna Deliverymentioning
confidence: 99%
“…In addition, AFM provides nanometer resolution structural, mechanical, and functional information about NLCs surfaces [46]. The NLCs usually appeared spherical in the TEM or SEM micrographs [47]. However, some studies found that the shape of NLCs was nonspherical, mainly cuboid.…”
Section: Morphologymentioning
confidence: 99%
“…The NLC solution was first centrifuged for 20 min at 14000 rpm. The free drug content was then determined by diluting the supernatant solution and using UV spectrophotometry at wavelength 214 nm (15). DEE was calculated using the following equation: DEE % = Total HU taken − Free HU Total HU taken × 100…”
Section: • Drug Entrapment Efficiencymentioning
confidence: 99%
“…In cancer therapy, NLCs have recently emerged as a multifunctional platform for drug delivery. Many advantages of this delivery system have been reported in earlier research, including excellent entrapment efficiency, good stability, and sustained release of drugs at specific rhythmic intervals [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%